My throat an open grave ebook - Bovalino, Tori (2024)
Labyrinth meets folk horror in this darkly romantic tale of a girl who wishes her baby brother away to the Lord of the Wood Growing up in the small town of Winston, Pennsylvania feels like drowning. Leah goes to church every Sunday, works when she isn't at school, and takes care of her baby brother, Owen. Like every girl in Winston, she tries to be right and good and holy. If she isn't the Lord of the Wood will take her, and she'll disappear like so many other girls before her. But living up to the rigorous standards of the town takes its toll. One night, when Owen won't stop screaming, Leah wishes him away, and the Lord listens. The screaming stops, and all that's left in the crib is a small bundle of sticks tied with a ribbon. Filled with shame and the weight of the town's judgment, Leah is forced to cross the river into the Lord of the Wood's domain to bring Owen back. But the devilish figure who has haunted Winston for generations isn't what she expects. He tells her she can have her brother back—for the price of a song. A song that Leah will have one month to write. It's a bargain that will uncover secrets her hometown has tried to keep buried for decades. And what she unearths will have her questioning everything she's been taught to fear.